A Qualitative Systematic Literature Review of the Role of U.S. Pharmacists in Prescribing Pre-Exposure Prophylaxis (PrEP) - Cernasev, Alina; Melton, Tyler C.; Jasmin, Hilary; Barenie, Rachel E. (Pharmacy, 2023)
Pre-Exposure Prophylaxis (PrEP) is an effective treatment to combat the human immunodeficiency virus (HIV) endemic, but the uptake of PrEP has been low in the United States (U.S.). While individuals may access PrEP via obtaining a prescription from their prescriber and having it dispensed by their pharmacist, less cumbersome access points may exist. This systematic literature review evaluates qualitative literature to explore the role of pharmacists, pharmacy services, and interprofessional collaborations for persons seeking PrEP in the United States. Four electronic databases (PubMed, Scopus, CINAHL, and Embase) were searched in February 2022 and yielded 3841 results. After excluding duplicates, two researchers reviewed 2461 studies. These results were screened for inclusion and exclusion criteria and yielded 71 studies for full review. Out of these 71 studies, five studies met the pre-selected inclusion criteria. Of the five studies, four were qualitative studies, and one was a mixed-methods study. The studies examined different aspects of initiating PrEP and diverse outcomes, such as screening for PrEP, barriers to access PrEP, feasibility to access PrEP, accessibility via community pharmacy to PrEP, and interdisciplinary collaboration between members of the healthcare team to expand patient access to PrEP. A gap in the qualitative literature focusing on U.S. pharmacists’ roles in initiation and provision of PrEP for diverse populations may exist. While PrEP promotion and uptake are largely affected by convenience and accessibility, future interventions and strategies should include training pertaining to PrEP screening, stigma reduction, privacy considerations, and PrEP dispensing.